AKIBAT HUKUM BAGI WARGA NEGARA YANG TERGABUNG SEBAGAI PEMBERONTAK DALAM PERSPEKTIF HUKUM INTERNASIONAL (STUDI KASUS PEMBERONTAKAN MELALUI AKSI TERORISME OLEH ISIS DI JAKARTA PUSAT) - I Komang Yudik Kresna Putra; Dewa Gede Sudika Mangku; Ni Putu Rai Yuliartini (Universitas Pendidikan Ganesha, 2023)
This study aims to identify and analyze the arrangements regarding rebel groups in the perspective of international law to analyze the legal consequences for Indonesian citizens who join as rebels according to international law as well. In this study, the type of research used is a type of normative legal research using a statutory approach (statute approach), case approach (case approach), and the conceptual approach (conseptual approach). The sources of legal materials used are primary legal materials, secondary legal materials and tertiary legal materials. The legal material collection technique used is a document study technique through library sources that are relevant to the issues discussed by analysis techniques of legal material obtained either in the form of primary legal material or secondary legal material which is analyzed qualitatively which will then be evaluated and interpreted and then argued carried out by researchers to provide a description of right or wrong and what is legally appropriate for the events that occur. The results of this study indicate (1) that in international law arrangements regarding rebels is regulated in additional protocol II of the 1949 Geneva Convention, but every party that takes a role in armed conflict including rebels has not been recognized as a subject of international law but is required to comply with international legal rules and (2) legal consequences for citizens who are involved as rebels is still not clear enough, so strict rules with severe sanctions are needed to prevent and punish the actions of the rebels and provide a deterrent effect to anyone involved in these activities.